Size Effects of Atomically Precise Gold Nanoclusters in Catalysis - Li, Site; Du, Xiangsha; Liu, Zhongyu; Li, Yingwei; Shao, Yucai; Jin, Rongchao (Precision Chemistry, 2023)
The emergence of ligand-protected, atomically precise gold nanoclusters (NCs) in recent years has attracted broad interest in catalysis due to their well-defined atomic structures and intriguing properties. Especially, the precise formulas of NCs provide an opportunity to study the size effects at the atomic level without complications by the polydispersity in conventional nanoparticles that obscures the relationship between the size/structure and properties. Herein, we summarize the catalytic size effects of atomically precise, thioate-protected gold NCs in the range of tens to hundreds of metal atoms. The catalytic reactions include electrochemical catalysis, photocatalysis, and thermocatalysis. With the precise sizes and structures, the fundamentals underlying the size effects are analyzed, such as the surface area, electronic properties, and active sites. In the catalytic reactions, one or more factors may exert catalytic effects simultaneously, hence leading to different catalytic-activity trends with the size change of NCs. The summary of literature work disentangles the underlying fundamental mechanisms and provides insights into the size effects. Future studies will lead to further understanding of the size effects and shed light on the catalytic active sites and ultimately promote catalyst design at the atomic level.